Sport psychological skills in jumping riders - Wolframm, I.; Ottersky, E. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
Empirical evidence suggests that there are a number of psychological skills that distinguish more elite from less successful, non-elite athletes. Few research efforts have focused on equestrian showjumping. Therefore, the aim of the study was to investigate sport psychological skills in jumping riders at different levels. American jumping riders (N=73; 16 male, 57 female; international: N=15, national: N=51, regional: N=7; showjumping: N=67, hunter: N=6) were recruited at two national shows to complete the Test of Performance Strategies (TOPS), an inventory designed to test sport psychological skill use during training and competition. The TOPS was adapted to equestrian sports and for use in competition only. The "TOPS-E", composed of nine sport psychological factors, with 4 items per factor, was tested for internal reliability using Cronbach`s alpha. The factors of self-talk, emotional control, automaticity, goal-setting, imagery, relaxation, negative thinking; attentional control showed good reliability (a=.71; .91; .74; .79; .68; .86; .84; .78). Activation had poor reliability (a=.36) and was removed from further analysis. The effect of gender, level and discipline on sport psychological skills was explored using multivariate analysis of variance. No violations of homogeneity and equality of variance were noted. Most important results showed a significant effect of competitive level on automaticity (F(2,67)=5.06; p=0.01). Post-hoc tests revealed significantly higher levels of automaticity for international compared to regional riders (16.4±3.36 vs. 11.71±2.49; p<0.01) and national and regional riders (15.43±2.68 vs. 11.71±2.49; p=0.01). Pearson`s correlations revealed significant correlations between years of participation and emotional control (r=.27; p<0.05), automaticity (r=.34; p<0.005), attentional control (r=.28; p<0.05) and negative thinking (r=-.31; p<0.01). Results indicate that more competent riders use automated sets of skills. Furthermore, attentional, emotional and thought control is likely to develop with experience. Layperson`s paragraph: Results indicate that the ability to use riding skills (aids) without consciously thinking about them when performing in the ring is an important element of jumping rider expertise. As with the ability to hold one`s focus, keep emotions and negative thoughts under control, automaticity seems to develop with years of practice.